Draft Tenth Five Year Plan 2002-2007 and Draft Annual Plan 2002-2003 Government of Haryana - Planning Commission (Planning Commission, 2002)
Ninth Five Year Plan outlay was approved at Rs. 11600.00 crore at current prices. This outlay included an amount of Rs . 4082.70 crore earmarked for Externally Aided Projects which means that Rs. 7517.30 crore were allocated for the Non-EAP schemes/projects. While formulating the plan, highest priority was accorded to the improvement/expansion of infrastructure of irrigation, power, roads & road transport by allocating a sum of Rs. 6761.62 crore which is 58.3% of the total outlay. The second highest priority was given to the social services sector and an amount of Rs. 3295.84 crore (28.4%) was earmarked for these services.
Planning Department, Government of Haryana